Kebijakan Pengelolaan Sumber Daya Air Sungai Mahakam di Kabupaten Mahakam Ulu - Laing, Piter; Gunawan, Andri; B, Jauchar (International Journal of Demos (IJD), 2025)
Abstract Mahakam Ulu Regency possesses abundant water resources, particularly from the Mahakam River, which is vital to the lives of local communities. However, pressures from population growth, natural resource exploitation, and industrial activities have led to pollution, deforestation, and a decline in water quality. This study employs a descriptive qualitative method. The findings highlight the importance of a holistic and sustainable approach to water resource management, involving active community participation, strengthening government capacity, and fostering collaboration among stakeholders. Policies that are responsive to changing environmental conditions and community needs will be more effective in ensuring the sustainability of water resources. With appropriate measures, Mahakam Ulu Regency is expected to manage its water resources more effectively for community welfare and environmental preservation. Furthermore, institutional strengthening, policy integration across sectors, and increased public awareness are necessary to maintain the sustainability of the Mahakam River. Adaptive and ecosystem-based management policies emerge as strategic solutions to ensure the continued ecological and social functions of the river in the future. Keyword: regulation, management, water resources Abstrak Kabupaten Mahakam Ulu memiliki sumber daya air melimpah, terutama dari sungai mahakam, yang vital bagi kehidupan masyarakat. Namun, tekanan dari pertumbuhan populasi, eksploitasi sumber daya alam, dan aktivitas industri menyebabkan pencemaran, deforestasi, dan penurunan kualitas air. Penelitian ini menggunakan metode deskriptif kualitatif. Penelitian ini menemukan pentingnya pendekatan holistik dan berkelanjutan dalam pengelolaan sumber daya air, dengan melibatkan partisipasi aktif masyarakat, peningkatan kapasitas pemerintah, dan kolaborasi antar pemangku kepentingan. Kebijakan yang responsif terhadap perubahan kondisi lingkungan dan kebutuhan masyarakat akan lebih efektif dalam memastikan keberlanjutan sumber daya air. Dengan langkah-langkah yang tepat, diharapkan Kabupaten Mahakam Ulu dapat mengelola sumber daya airnya secara lebih efektif untuk kesejahteraan masyarakat dan kelestarian lingkungan selain itu diperlukan penguatan kelembagaan, integrasi kebijakan antar sektor, serta peningkatan kesadaran masyarakat dalam menjaga keberlanjutan Sungai Mahakam. Kebijakan pengelolaan yang adaptif dan berbasis ekosistem menjadi solusi strategis untuk menjamin keberlangsungan fungsi ekologis dan sosial sungai di masa mendatang. Kata Kunci: kebijakan, pengelolaan, sumber daya air